The values expectations of high school graduates at the choice of the faculty and future occupation - Petrović, Nebojša B.; Čabarkapa, Milanko D.; Kuzmanović, Bora R. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
There are many psychological references to professional orientation of pupils. However, mainly studied predictors were the role of school, peers, parents, socio-economics factors, and less the role of personality traits, goals, expectations, personal and social values. In this paper the focus is on personal goals and social values defined as specific objectives that are significant for a faculty choice, and therefore a future profession. We use two lists of goals - 18 personal and 18 social, applied to the sample of 497 high school pupils in fourth grade. The study was conducted in school settings. Preference and level of importance of the objectives of respondents have been expressed on the 5-point scale of Likert type, which allowed the statistical analysis of applied methods. The research results show significant differences in individual preferences of the goals and values, as well as the significantly connection of the goals with expectations to be fulfilled by faculty and future career choice. In addition, it was shown that the higher importance is given to personal than social values, which justified starting assumption of the authors, to examine personal and social values separately, since they were shown to have a different significance for professional orientation of young people.